Workshop Peningkatan Keterampilan Debat bagi Siswa SMK Muhammadiyah 1 dan 3 Ciputat - Nur Amalia; Nawawi Nawawi; Nur Aini Puspitasari (Universitas Sarjanawiyata Tamansiswa, 2019)
Workshop on Improving Skills Debate of SMK Muhammadiyah 1 and 3 Ciputat. Which of course is very interesting for students. Through this method students do not feel patronized but they are expected to have their own way how to understand the implementation of an interesting debate because students find themselves an interesting debate style and presented in an interesting way that teachers and students need to develop, this can add self-confidence to students. At the time of implementation, the practice of the debate focused on students' activeness in speaking / arguing in the debate. Both groups who will argue either as a negation group or affirmation group play an active role and produce brilliant ideas. After the debate practice, the team will provide its assessment and commentary on the practice of the debate that has been done. Assessment is given as objectively as possible based on a prepared table. The aspects assessed include: The accuracy and authenticity of ideas, the ability to argue, understanding, accuracy of words and sentences, and fluency in conveying ideas. The results obtained after the students were taught using inquiry method and interactive video learning media, there was an increase of results and according to what was expected. The results of the training activities were responded and the questions conveyed by the participants to the Community Service Team (Tim Pengabdian Masyarakat = TPM). Responses and questions indicate high interest and curiosity towards the improvement of student debate skills of SMK Muhammadiyah 1 and 3 Ciputat. Thus this training activity is considered successful. The expected outcomes from this Community Service Activity are students of SMK Muhammadiyah 1 Ciputat and SMK Muhammadiyah 3 Ciputat can improve their speaking ability through debate activities. In addition the team will create a scientific article that will be published in the journal ISSNKey word: Debate, Inquiry, Skills, Video Interactive